Overlapping and distinct intrinsic connectivity of hippocampal and triple networks in autistic individuals with and without a comorbid condition of ADHD - Lang Chen; Anna Riggs; Nickolas Luckenbach (Frontiers in Psychiatry, 2026)
Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) are conventionally thought to be very distinct neurodevelopmental disorders, but many autistic individuals also exhibit symptoms of ADHD. Extensive research has focused on examining the behavioral profiles of autistic individuals with comorbid ADHD, but their neurobiological profiles remain understudied. The current study aimed to examine the intrinsic connectivity of the hippocampal memory, default-mode, central executive, and salience networks in autistic individuals with or without ADHD. Using data from the Autism Brain Imaging Data Exchange (ABIDE I), we identified 23 individuals with autistic disorder and comorbid ADHD (Comorbid), 23 individuals with autistic disorder only (ASD-only), and 23 non-autistic individuals (non-ASD), who were well-matched on gender, age, and full-scale IQ. Results showed that the Comorbid group showed hypo-connectivity of the hippocampal memory, DMN, CEN, and SN nodes compared to the ASD-only group. In addition, the connectivity of the right hippocampus and PCC showed distinct relationships with the ASD symptom severity in autistic individuals with and without ADHD. These findings indicated that the comorbid condition has a distinct neurobiological profile compared to the ASD-only group, suggesting that future intervention and education should have specialized programs to support affected individuals with a focus on their memory functions in addition to their socio-communicative challenges.